A Life Threatening Rash, an Unexpected Cause - Dhiraj Jain; Stalin Viswanathan; Chandramohan Ramasamy (Hindawi Limited, 2014)
We describe a 74-year-old man with purpura fulminans and altered sensorium following an acute febrile illness. Intensive sepsis management was to no avail, until institution of doxycycline therapy following confirmation of scrub typhus. Empirical doxycycline needs to be considered in endemic areas for patients presenting with purpura fulminans.